The investigation of vasospastic effect of hemostatic matrix used in intracranial operations on cerebral arteries - Akyoldas, Goktug; Kalemci, Orhan; Ersen Danyeli, Ayca; Acis, Onur; Kizmazoglu, Ceren; Ur, Koray; Nuri Arda, Mehmet (Annals of Medical Research, 2021)
Aim: We aimed to investigate the vasospastic effect of thrombin-based hemostatic matrix on the basilar arteries in rats.Material and Methods: A total of 28 female albino Wistar rats were used in the study. The rats were randomly assigned to four groups. The rats in group I (control group) were sacrificed without surgical manipulation. We injected 0.1 mL of nonheparinized autologous arterial blood into the cisterna magna of the rats in group II, 0.1 mL of hemostatic matrix into the cisterna magna of the rats in group III, and 0.1 mL of a mixture of nonheparinized autologous arterial blood and the hemostatic matrix into the cisterna magna of the rats in group IV. The experimental rats were sacrificed 48 hours after injections. Three sections were obtained from each rat’s basilar arteries and photographed under a light microscope. Basilar artery cross-section areas were measured using computerized image analysis systems.Results: Mean basilar artery cross-sections of all groups revealed statistically a significant difference between only group I and group II. The mean basilar artery cross-sec-tion areas of groups II, III, and IV decreased by 36%, 19%, and 22%, respectively, in comparison with those of group I.Conclusion: Although our results pertaining to thrombin-based hemostatic matrix were not statistically significant, it is hypothesized that this matrix has a vasospastic effect on arteries. Therefore, it important to remember that when such a matrix is used in cranial surgery, the thrombin contained therein could have a vasospastic effect on cerebral arteries.Keywords: Cerebral vasospasm; hemostatic matrix; thrombin; rat; subarachnoid hemorrhage.